Current Perspectives on Letermovir and Maribavir for the Management of Cytomegalovirus Infection in Solid Organ Transplant Recipients - Razonable RR (Drug Design, Development and Therapy, 2024)
Raymund R Razonable1,2 1Division of Public Health, Infectious Diseases and Occupational Medicine, Mayo Clinic, Rochester, MN, USA; 2William J von Liebig Center for Transplantation and Clinical Regeneration, Mayo Clinic, Rochester, MN, USACorrespondence: Raymund R Razonable, Email razonable.raymund@mayo.eduAbstract: Cytomegalovirus (CMV) infection is arguably the most important infectious complication that negatively affects the outcome of solid organ transplantation. For decades, CMV management after transplantation has relied on antiviral drugs that inhibit viral DNA polymerase (ganciclovir, foscarnet, and cidofovir). However, their use has been complicated by myelosuppression, nephrotoxicity, and selection of drug-resistant viruses. During the past few years, the therapeutic armamentarium for the management of CMV in solid organ transplant recipients has expanded with the approval of letermovir for CMV prophylaxis in high-risk CMV D+/R- kidney recipients, and maribavir for the treatment of refractory and resistant CMV infection. Both drugs offer significant improvement when compared to standard anti-CMV therapies; letermovir was as efficacious for CMV prevention, whereas maribavir was more effective in treating refractory and resistant CMV infections. Both letermovir and maribavir have favorable safety profiles compared to CMV DNA polymerase inhibitors, without the risk of neutropenia and leukopenia associated with ganciclovir and renal toxicities associated with foscarnet and cidofovir. Moreover, letermovir and maribavir are orally bioavailable, which allows convenient outpatient treatment. However, letermovir and maribavir have a significant drug interaction potential in solid organ transplant recipients, resulting in higher levels of calcineurin inhibitors (cyclosporine and tacrolimus) and mTOR inhibitors (sirolimus and everolimus). Both letermovir and maribavir are CMV-specific and do not have clinical efficacy against other herpes viruses. Thus, there is a need for additional antiviral drugs to prevent herpes simplex and other herpes viruses when clinically indicated. This article provides a comprehensive review of the clinical data supporting the use of letermovir and maribavir in clinical practice. The author provides perspectives on the role of these newly approved drugs in the current management landscape of CMV infection in solid organ transplantation.Keywords: cytomegalovirus, maribavir, letermovir, ganciclovir, drug resistance, prophylaxis, treatment